2007
DOI: 10.1007/s10886-007-9398-7
|View full text |Cite
|
Sign up to set email alerts
|

New Sex Attractant Composition for the Click Beetle Agriotes proximus: Similarity to the Pheromone of Agriotes lineatus

Abstract: While testing traps baited with a blend of geranyl octanoate and geranyl butanoate (pheromone components previously identified for Agriotes lineatus, Coleoptera, Elateridae) in Portugal and Bulgaria, large numbers of the closely related Agriotes proximus were captured. In the literature, two different compounds, (E,E)-farnesyl acetate and neryl isovalerate had previously been identified as pheromone components of A. proximus. Subsequent field tests, conducted in several European countries, revealed that A. pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 7 publications
3
27
0
Order By: Relevance
“…These results were unexpected, since, in chemical studies, this compound was detected only in trace amounts in female pheromone glands Yatsynin et al 1996b;Tóth et al 2003). Similarly, A. proximus males showed the strongest attraction to the 1:1 blend in the field (Tóth et al 2008). In contrast in this present study, geranyl octanoate was detected in high amounts, and geranyl butanoate was present only in traces (less than 0.1% of geranyl octanoate) in gland extracts of the females.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These results were unexpected, since, in chemical studies, this compound was detected only in trace amounts in female pheromone glands Yatsynin et al 1996b;Tóth et al 2003). Similarly, A. proximus males showed the strongest attraction to the 1:1 blend in the field (Tóth et al 2008). In contrast in this present study, geranyl octanoate was detected in high amounts, and geranyl butanoate was present only in traces (less than 0.1% of geranyl octanoate) in gland extracts of the females.…”
Section: Discussionmentioning
confidence: 96%
“…In previous field trials that tested different ratios of geranyl butanoate and geranyl octanoate, the greatest catches of A. lineatus were obtained with a blend containing relatively large amounts of geranyl butanoate (ratio of 1:1) (Tóth et al 2008). These results were unexpected, since, in chemical studies, this compound was detected only in trace amounts in female pheromone glands Yatsynin et al 1996b;Tóth et al 2003).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…According to Staudacher et al (2011a), PCR analyses showed a high similarity between A. lineatus and A. proximus. Additionally, both species were found to be attracted to the same pheromone composition (Tóth et al 2008, Vuts et al 2012. Agriotes obscurus, A. lineatus and A. sputator have also become established in some parts of Canada and the USA.…”
Section: Distributionmentioning
confidence: 94%